2020
DOI: 10.1017/s136898002000021x
|View full text |Cite
|
Sign up to set email alerts
|

The association of parenting practices with toddlers’ dietary intake and BMI, and the moderating role of general parenting and child temperament

Abstract: Objective: The objective was to examine the association between parenting practices, toddler’s dietary intake and BMI. In addition, potential moderation of these associations by general parenting and child temperament was examined. Design: The current cross-sectional study assessed parenting practices using the Comprehensive Feeding Practices Questionnaire, general parenting using the Comprehensive General Parenting Questionnaire, child temperament using the Child Behavior Check List, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…Other studies suggest that parental feeding practices may differ according to child's sex and that, for the same parental feeding practice, child's response may depend on their sex [18,19]. Moreover, several cross-sectional studies have found that coercive parental feeding practices, such as restriction or pressure to eat, are related to child's weight status (e.g., parental restrictive feeding practices are associated to higher child's BMI, whereas parental pressure to eat is associated to lower child's BMI) [20][21][22], child's intake (e.g., parental restrictive practices are associated with increased child's energy intake) [23][24][25] or eating behavior (e.g., parental pressure to eat may enhance food dislikes) [26,27]. Some longitudinal studies found that coercive feeding practices led to lower childhood BMI [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies suggest that parental feeding practices may differ according to child's sex and that, for the same parental feeding practice, child's response may depend on their sex [18,19]. Moreover, several cross-sectional studies have found that coercive parental feeding practices, such as restriction or pressure to eat, are related to child's weight status (e.g., parental restrictive feeding practices are associated to higher child's BMI, whereas parental pressure to eat is associated to lower child's BMI) [20][21][22], child's intake (e.g., parental restrictive practices are associated with increased child's energy intake) [23][24][25] or eating behavior (e.g., parental pressure to eat may enhance food dislikes) [26,27]. Some longitudinal studies found that coercive feeding practices led to lower childhood BMI [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It was aimed at parents of children aged 5 to 13 years, and it has been used as such to examine associations between the five parenting constructs and children’s health behaviors [ 31 ]. Some studies used only the “positive” parenting constructs (nurturance, structure and behavioral control) in examining associations between parenting practices, health behaviors and BMI and the role of general parenting, which meant that the two negative (control constructs (coercive control and overprotection) were unexplored [ 27 , 32 ]. A version for parents of children aged one and four to five was later developed, which included 69 items [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This contextual model in which parenting style is a moderator has been brought up in several studies examining the associations between parenting practices and children's EBRBs [8,[19][20][21]. Although some studies have found that parenting style is moderating the association between parenting practices and children's and adolescent's food intake or BMI [22][23][24][25][26], to the best of our knowledge, only one study has examined young children (one-to three-year-olds) [27].…”
Section: Introductionmentioning
confidence: 99%
“…Parents play a crucial role in shaping children's early experience with foods [16,17]. Mothers are the major caregivers of young children, and maternal feeding practices may play the most essential role in toddlers' dietary intake and weight status [18].…”
Section: Introductionmentioning
confidence: 99%